THINGS AS SYMBOLS OF «THE REALIZED CONNECTION» BETWEEN BEING AND NONEXISTENCE. - Якуша, Ю. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article is devoted to discovering the deepest demention of the world’s things through opening their symbolic nature.